Clinical progression and viral load in a community outbreak of coronavirus-associated SARS pneumonia: a prospective study - Peiris, JSM (Lancet, 2003)
BACKGROUND: We investigated the temporal progression of the clinical, radiological, and virological changes in a community outbreak of severe acute respiratory syndrome (SARS). METHODS: We followed up 75 patients for 3 weeks managed with a standard treatment protocol of ribavirin and corticosteroids, and assessed the pattern of clinical disease, viral load, risk factors for poor clinical outcome, and the usefulness of virological diagnostic methods. FINDINGS: Fever and pneumonia initially improved but 64 (85%) patients developed recurrent fever after a mean of 8.9 (SD 3.1) days, 55 (73%) had watery diarrhoea after 7.5 (2.3) days, 60 (80%) had radiological worsening after 7.4 (2.2) days, and respiratory symptoms worsened in 34 (45%) after 8.6 (3.0) days. In 34 (45%) patients, improvement of initial pulmonary lesions was associated with appearance of new radiological lesions at other sites. Nine (12%) patients developed spontaneous pneumomediastinum and 15 (20%) developed acute respiratory distress syndrome (ARDS) in week 3. Quantitative reverse-transcriptase (RT) PCR of nasopharyngeal aspirates in 14 patients (four with ARDS) showed peak viral load at day 10, and at day 15 a load lower than at admission. Age and chronic hepatitis B virus infection treated with lamivudine were independent significant risk factors for progression to ARDS (p=0.001). SARS-associated coronavirus in faeces was seen on RT-PCR in 65 (97%) of 67 patients at day 14. The mean time to seroconversion was 20 days. INTERPRETATION: The consistent clinical progression, shifting radiological infiltrates, and an inverted V viral-load profile suggest that worsening in week 2 is unrelated to uncontrolled viral replication but may be related to immunopathological damage. Published online May 9, 2003 http://image.thelancet.com/extras/03art4432web.pdf